PENGARUH LITERASI KEUANGAN DAN PERILAKU KONSUMTIF TERHADAP PENGELOLAAN KEUANGAN PRIBADI MAHASISWA AKUNTANSI DI UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - Yolanda Maghdalena Sihaloho; Hwihanus , Hwihanus (Publikasi Inspirasi Indonesia, 2024)
This study examines the effect of financial literacy and consumptive behavior on the personal financial management of accounting students at Universitas 17 Agustus 1945 Surabaya. Using a qualitative approach with a case study design, this study involved 30 accounting students in semester 5 who managed their personal finances independently. Data were collected through questionnaires covering aspects of financial literacy, consumptive behavior, and financial management strategies. The results showed that students have an awareness of the importance of financial literacy, although the frequency of reading financial articles is still relatively low. Factors such as promos, discounts, personal needs, and product quality influence their shopping decisions. Social media and online advertising have a significant influence on students' consumptive behavior. In financial management, students apply various strategies such as looking for promos, avoiding impulse purchases, and making a monthly budget. The way of dividing money between spending and saving varies, with the percentage method and prioritization of basic needs as common approaches. While there is an understanding of the importance of financial literacy, its application in daily practice is mixed, suggesting challenges in turning knowledge into concrete behavior. This study highlights the importance of improving practical financial literacy education for university students to face the challenges of financial management in the digital era, especially in controlling consumptive behavior.